When Leadership Drives Nurses Away: Empirical Research Qualitative on High Turnover Rates Reasons - Saleem Al‐Rjoub (Nursing Open, 2025)
ABSTRACT Aim This study aimed to investigate the reasons that affect nurses' decisions to leave their setting. Nurse turnover impacts organisational costs, organisational stability, and quality of care. The role of nurse leaders' practices in nurse turnover remains underexplored. Design Descriptive phenomenological design was used in the current study. Method Giorgi's phenomenological method was used to explore the staff nurses' lived experiences and perceptions of turnover. The data was collected from semi‐structured interviews with nurses who had left their current positions, moved to another organisation, changed professions, or retired. Results Five themes emerged from the analysis: (1) poor communication, (2) a lack of leader support, (3) workloads and staffing issues, (4) a lack of professional development opportunities, and (5) inconsistent policies and leadership. Conclusion Nurse leaders and administration play a critical role in driving nurses to stay or to leave the healthcare organisation by providing different and important practices and behaviours. Reducing the nursing turnover rate can create a more stable environment and enhance nurse satisfaction, which leads to better patient care. Implications for Nursing Administration Nursing administration must create supportive workplace environments by enhancing leadership practices to reduce the nursing turnover rates, especially among new graduate nurses. Impact The current study addresses the nurse turnover issue, with a particular focus on the role of nurse leaders' practices in nurse turnover. High nursing turnover rates impact organisational costs, organisational stability, and quality of care. This study will have a significant impact on nursing leadership, healthcare administration and policymakers. Patient or Public Contribution No Patient or Public Contribution.